2021
DOI: 10.1186/s40816-021-00310-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phospholipase A2, platelet aggregation and egg albumin induced rat paw oedema as anti-inflammatory effect of Peltophorun pterocarpus stem-bark

Abstract: Background Most medicinal plants presently employed in traditional medicine are used without scientific evidence, thereby suggesting a need to explore efficient and reliable investigations of their potential. We, therefore, conducted the present study to ascertain the efficacy of flavonoid-rich extract of Peltophorum pterocarpum sterm-bark in the treatment and management of inflammatory disorders as employed in folk medicine. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Many recent studies have reported the activity of various flavonoid derivative compounds having good activity in inhibiting this enzyme and treating inflammation [ 173 , 174 ]. A study conducted by Enechi and reported colleagues [ 175 ] that flavonoid-rich extract from Peltophorum pterocarpum stem-bark provide a strong inhibitory effect in PLA2 and generate downmodulate of the inflamematory symptoms of paw oedema induced by egg albumin, in comparison with prednisolone as well approve anti-inflammatory drugs that act in PLA2. In accordance, several other studies have also demonstrated compounds such as quercetin, kaempferol, and galangin showing promising inhibitory activity against PLA2 [ 173 , 174 , 176 ].…”
Section: Flavonoid Derivates As Anti-inflammatory Agents and Their Me...mentioning
confidence: 99%
“…Many recent studies have reported the activity of various flavonoid derivative compounds having good activity in inhibiting this enzyme and treating inflammation [ 173 , 174 ]. A study conducted by Enechi and reported colleagues [ 175 ] that flavonoid-rich extract from Peltophorum pterocarpum stem-bark provide a strong inhibitory effect in PLA2 and generate downmodulate of the inflamematory symptoms of paw oedema induced by egg albumin, in comparison with prednisolone as well approve anti-inflammatory drugs that act in PLA2. In accordance, several other studies have also demonstrated compounds such as quercetin, kaempferol, and galangin showing promising inhibitory activity against PLA2 [ 173 , 174 , 176 ].…”
Section: Flavonoid Derivates As Anti-inflammatory Agents and Their Me...mentioning
confidence: 99%
“…Methanol Extract of Rauwolfia vomitoria leaves on Phospholipase A2 (PLA2) Activity: The effect of MERVL on PLA2 activity was carried out using method of Vane [12] with little adjustments by Enechi et al [13]. Fresh blood samples were taken from healthy people and centrifuged for 10 minutes at 3000 rpm.…”
Section: Anti Inflammatory Assaysmentioning
confidence: 99%
“…The effect of FRFPML on PLA 2 activity was evaluated using method of Vane [34] with modifications by Enechi et al [35]. Fresh human blood samples collected from healthy individuals were centrifuged at 3000 rpm for 10 min afterwards; the supernatant (plasma) was discarded.…”
Section: The Effect Of Frfpml Phospholipase a 2 (Pla 2 ) Activitymentioning
confidence: 99%